CO06 | Recurrences of catheter associated upper extremity deep vein thrombosis in cancer: a two year prospective study with enoxaparin (Bleeding, Thrombosis and Vascular Biology)
Background: The upper extremity deep vein thrombosis (UEDVT) in association with use of central venous catheters is a frequent finding in patients with cancer. Current guidelines suggest three month anticoagulation for the treatment of catheter-related UEDVT (CRT) in cancer patients, but few data are available on the appropriate anticoagulant strategy beyond three months.